Correlation Between Potato And Salinity : Investigating The Myth In The Internet - Afifah Binti Abdul Azmil; Nurul `Izzan Binti Abdul Razak; Muhammad Safwan Bin Khairudin; Anis Safiyah Binti Hilmi; Nur Aliya Nabila Binti Mohd Fauzi; Muhammad Azan Tamar Jaya (Kolej Genius Insan, Universiti Sains Islam Malaysia, 2024)
2nd Insan Junior Researchers International Conference 2021 (iJURECON 2021) “STREAM for a Better Life” 15-17th October 2021 Organized By :Kolej GENIUS Insan of Universiti Sains Islam Malaysia